Loan Default and Its' Determinants among Small-Scale Farm Households in Kilinochchi District - Umashankar, K.; Sugirthan, P. (Sri Lanka Agricultural Economics Association, 2014)
This study focused on the farmers' credit default issues in the Kilinochchi District. This feature is intensively felt in the Kilinochchi District because majority of the farmers have lost their properties and livelihood and resettled recently. There were various arguments related to the term loan. But the need for the term 'loan' especially in Kilinochchi District was most indispensable, due to lack of access to farmers to equity capital. Factors such as unexpected weather, severe drought, floods, pest and disease incidents and unpredictable climatic conditions aggravate the situation. Currently failing repayments has reduced the supplies of credit. A better credit culture is therefore imperative in order to sustain farming. This study was conducted with objectives to find: (i) the default probability of the farmers (ii). socioeconomic factors influencing the default behavior and (iii). To propose measures to achieve a better credit culture among the farmers. 240 respondents were selected through stratified random sampling. Number of borrowers in each DS division was considered. Data were collected through open ended, and open ended with prequalifying statements. Data were collected on farmers' socio economic factors, loan repayment and default issues. The collected data were analyzed using probit regression model. The econometric software STATA was used. Results revealed that the overall default probability of the farmers exceeds 62 percent and the farmer's default behavior depended on age, household size and borrowing interest rate, influencing positively and being statistically significant. Again gender, civil status, loan duration, experience and household total income influenced negatively and were statistically significant. It is recommended that measures that could improve the farmers' position such as income, provision of mobile credit services, increasing the repayment period reasonably, reducing the interest rates and targeting young and experienced farmers as the credit recipients in the district. These measures would be expected to reduce the default rate and lead the way to a better credit culture.
Keywords: Agricultural credit; Credit default; Probit regression model; Kilinochchi District